(3GdVQhQGJ aj GdebJQfGJs - (3GdaRGQj , EHQGgje Hf YHO GdQMef Hf EHQGgje Hf SHGY Hf GdaQcGM, HQgGf GdOjf CHh ESMGb,J (B729 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI CeG VQhQI CehGd JYOd MOhOkG aEfG EPG bdfG eGd jYOd KdGKI CMOGO s
(3BNQgG (B:s
(3hgPg UhQI GdTcd s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B45 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B43s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3LGQ Gddg (B(1505) s
Keywords: (3eJaQbGJs